2023
DOI: 10.1126/science.adg4520
|View full text |Cite
|
Sign up to set email alerts
|

Chemically circular, mechanically tough, and melt-processable polyhydroxyalkanoates

Abstract: Polyhydroxyalkanoates (PHAs) have attracted increasing interest as sustainable plastics because of their biorenewability and biodegradability in the ambient environment. However, current semicrystalline PHAs face three long-standing challenges to broad commercial implementation and application: lack of melt processability, mechanical brittleness, and unrealized recyclability, the last of which is essential for achieving a circular plastics economy. Here we report a synthetic PHA platform that addresses the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 55 publications
1
79
0
Order By: Relevance
“…27 Chen and co-workers recently presented the ring-opening polymerization (ROP) of α, α-dialkyl substituted β-butyrolactone to produce semicrystalline polyhydroxyalkanoates with enhanced thermal stability, melt-processability, closed-loop recyclability as well as high ductility and toughness that are comparable to commodity polyolefin plastics. 28 However, in contrast to the active research and great advancements achieved in academia, the scalable production in the industry for these closed-loop recyclable polymers proceeds slowly, which greatly hampers their practical applications. One possible reason is the complicated, expensive, and time-consuming scalable process from laboratory to industry for these completely new monomers, especially those with tedious synthetic procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Chen and co-workers recently presented the ring-opening polymerization (ROP) of α, α-dialkyl substituted β-butyrolactone to produce semicrystalline polyhydroxyalkanoates with enhanced thermal stability, melt-processability, closed-loop recyclability as well as high ductility and toughness that are comparable to commodity polyolefin plastics. 28 However, in contrast to the active research and great advancements achieved in academia, the scalable production in the industry for these closed-loop recyclable polymers proceeds slowly, which greatly hampers their practical applications. One possible reason is the complicated, expensive, and time-consuming scalable process from laboratory to industry for these completely new monomers, especially those with tedious synthetic procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Lu et al reported the design of 4-hydroxyproline-derived bridged bicyclic thiolactones and their controlled polymerization to produce closed-loop recyclable polythioesters under mild conditions . Chen and co-workers recently presented the ring-opening polymerization (ROP) of α, α-dialkyl substituted β-butyrolactone to produce semicrystalline polyhydroxyalkanoates with enhanced thermal stability, melt-processability, closed-loop recyclability as well as high ductility and toughness that are comparable to commodity polyolefin plastics . However, in contrast to the active research and great advancements achieved in academia, the scalable production in the industry for these closed-loop recyclable polymers proceeds slowly, which greatly hampers their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The activation or deactivation of the initiator is strongly dependent on the type of FAs used (Figure 3f), while all FAs can activate the monomer (Figure 3g; for more discussions, see the Supporting Information, Monomer/ Initiator Activation section, and Figures S28 and S29). The affinity of FA for cyclic esters (simulated by VL rather than GL to avoid polymerization) and polymer main chain esters (simulated by ethyl acetate) was also determined through 13 C NMR titration (Figure S30). The association constant (K ass ) of FA and cyclic ester was measured to be 6.2 M −1 , which is 1.7 times higher than that for main chain esters (3.6 M −1 ), indicating a selective activation of monomers (s-cis esters) over polyesters (s-trans esters) by FA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, ∼82% of plastics on the market are of single use and not recycled, creating extremely negative impacts on the health and the environment. The design and use of biodegradable and chemically recyclable polymers is a promising approach for the circular economy of plastics and for achieving a sustainable world. This approach has been successfully applied in polyesters, polythioesters, polyacetals, polycarbonates, and polyolefins . Among them, aliphatic polyesters are an important class of biocompatible, biodegradable commodity polymers usually obtained by living anionic ring-opening polymerization (ROP) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al discovered that when more than 10 wt % PHA was added into PLA during melt spinning, the initial modulus of the blended fibers decreased from 78 to 67 cN/dtex. However, current PHAs are intrinsically thermally unstable, with a relatively low degradation temperature (T d , the temperature at 5% weight loss) of ∼250 °C, owing to the presence of α-hydrogens that promote facile cis-elimination via the six-membered transition state to form an internal alkene and a carboxylic acid, causing a large, continuous drop in shear viscosity under melt-processing conditions . Once the PHA is degraded, it will further accelerate the degradation of PLA in the blend system. Simultaneously, the melt viscosity of PHAs decreases significantly, resulting in decreased melt strength of the PLA/PHA blend system and poor spinning stability of the fibers .…”
Section: Introductionmentioning
confidence: 99%